2019
DOI: 10.34311/jics.2019.02.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Activated Carbon from Sago Waste (Metroxylon sagu) with ZnCl2 Activation and HNO3 Modification

Abstract: Previous researches have shown that activated carbon could be made from various raw materials which contain lignocellulose. The aims of this research were to synthesis and characterize the activated carbon obtained from lignocellulose contained in sago waste. The synthesis was conducted through multiple stages of dehydration, carbonization, silica extraction with NaOH, activation by ZnCl2 10%, and surface modification using HNO3 65%, successively. From X-ray fluorescence, it was confirmed that treatment with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(24 reference statements)
1
4
0
2
Order By: Relevance
“…The ashes and A.C. (III) and (IV) showed a high distribution of pores on the surface; this is a common characteristic of materials that have an excellent adsorptive capacity, as reported previously [38][39][40][41]. However, the A.C. (I) and (II) did not show a significant number of pores on their surface, probably due to the type of treatment that the materials were submitted [42,43]. The EDS analysis allowed us to determine the elemental composition of the adsorbents and the results are shown in Table III.…”
Section: Adsorbent Characterizationsupporting
confidence: 74%
“…The ashes and A.C. (III) and (IV) showed a high distribution of pores on the surface; this is a common characteristic of materials that have an excellent adsorptive capacity, as reported previously [38][39][40][41]. However, the A.C. (I) and (II) did not show a significant number of pores on their surface, probably due to the type of treatment that the materials were submitted [42,43]. The EDS analysis allowed us to determine the elemental composition of the adsorbents and the results are shown in Table III.…”
Section: Adsorbent Characterizationsupporting
confidence: 74%
“…Before activation process, silica extraction was performed by mixing the carbon powder with NaOH solution to remove the high silica content in waste sago carbon. As this study used the same method, the details of silica extraction process can be found in previous report (Allo et al, 2019). .…”
Section: Activation Processmentioning
confidence: 99%
“…In this study, the activated carbon was prepared from waste sago, as an endemic plant in Southeastern Asia and a very commonly found as local food in Papua and Maluku, however the waste generated has not been used optimally. Moreover, waste sago chosen as precursor materials due to its lignocellulose content (Allo et al, 2019). Waste sago carbon were activated using two different chemical activations called phosphoric acid (H3PO4) and potassium hydroxide (KOH).…”
Section: Introductionmentioning
confidence: 99%
“…Tabel 1 menunjukkan bahwa ekstraksi silika berhasil dilakukan, dengan hanya 1% berat Si tersisa. Hal ini berarti penambahan larutan NaOH dapat mengikat silika dioksida dari ampas sagu, dan kemudian dilarutkan serta dibuang bersama-sama dalam proses pencucian dengan akuades (Allo, Sudarmono & Togibasa, 2019). Unsur Ca dan Si merupakan unsur elektroda karbon yang umum terdapat dari ampas sagu (Rifani, Taer, & Taslim, 2018).…”
Section: Hasil Dan Pembahasan Ekstraksiunclassified
“…Gambar 3 Hasil SEM karbon aktif dengan perbesaran 5.000x dengan konsentrasi ZnCl2 yaitu: (a) 5%, (b) 15%, dan (c) 20% yang tersisa, yang artinya muncul pengikatan parsial. Hal ini dapat saja disebabkan karena proses pencucian dan penetralan yang belum optimal (Allo, Sudarmono & Togibasa, 2019).…”
Section: Karakterisasi Karbon Aktifunclassified